Chemical composition and antifungal activity of the essential oil of Bauhinia forficata Flowers (Link) and its properties in the germination of Cucurbita maxima (Duchesne) seeds (Research, Society and Development, 2022)
Agroecological production has been increasing a lot in recent years, confirming the need for safer and more effective measures to control agricultural pests through the use of natural products such as essential oils. This study aimed to evaluate the chemical composition of the essential oil of Bauhinia forficata flowers, its antifungal activity, as well as its effect on the germination of Curcubita maxima seeds. The essential oil was extracted by hydrodistillation and analyzed by gas chromatography coupled with mass spectrometry (GC-EM). They were later evaluated at different concentrations for antifungal activity against Sclerotinia sclerotiorum, Rhizopus microsporus and Colletotrichum gloeosporioides. In the germination development assay, the seeds of C. maxima were immersed in different doses of essential oil and their germination and developments were compared with commercial fungicide Vitavax thiram®. The major compounds identified were guaia-1(10),11-diene (66.17%), α-pinene (14.06%) and β-pinene (4.14%). The essential oil from the flowers of B. forficata at the highest concentrations inhibited the mycelial growth of the fungi R. Microsporus, C. gloeosporioides and S. Sclerotiorum by 37.71%; 73.7% and 25.74%, respectively. The essential oil from B. forficata flowers at a dose of 30 µL favored germination and seedling development without significant difference compared to the commercial fungicide Vitavax thiram®, which implies greater and healthier production. These results indicate that the essential oil of B. forficata has positive aspects for agroecological production, which leads to great evolutionary perspectives for the sustainable environment.